High temperature enhances the ability of Trichoderma asperellum to infect Pleurotus ostreatus mycelia - Qiu, Zhiheng (PLoS One, 2017)
Trichoderma asperellum is one of the species which can be isolated from contaminated Pleurotus ostreatus cultivation substrate with green mold disease. This study focused on the relationship between high temperature and infectivity of T. asperellum to P. ostreatus. Antagonism experiments between T. asperellum and P. ostreatus mycelia revealed that high temperature-treated P. ostreatus mycelia were more easily infected by T. asperellum and covered by conidia. Microscopic observation also showed that P. ostreatus mycelia treated with high temperature could adsorb more T. asperellum conidia. Furthermore, conidia obtained from T. asperellum mycelia grown at 36°C featured higher germination rate compared with that incubated at 28°C. High temperature-treated T. asperellum mycelia can produce conidia in shorter periods, and T. asperellum mycelia were less sensitive to high temperature than P. ostreatus. Deactivated P. ostreatus mycelia can induce T. asperellum cell wall-degrading enzymes (CWDEs) and P. ostreatus mycelia subjected to high temperature showed induced CWDEs more effective than those incubated at 28°C. Moreover, T. asperellum showed higher CWDEs activity at high temperature. In dual cultures, hydrogen peroxide (H(2)O(2)) increased after 36°C, and high concentration of H(2)O(2) could significantly inhibit the growth of P. ostreatus mycelia. In summary, our findings indicated for the first time that high temperature can induce a series of mechanisms to enhance infection abilities of T. asperellum to P. ostreatus mycelia and to cause Pleurotus green mold disease.